Analysing Youtube audience based on lifestyle, uses and gratification theory - Bostan, İlkin (My University, 2020)
İnsanlar farklı koşullarda ve yaşam tarzlarında yaşarlar. Pazarlama için, potansiyel tüketici hareketlerini incelemek (gözlemlemek) çok önemlidir çünkü markalar bu tahminlerle stratejilerine karar verirler. Her tüketicinin kendine özgü özellikleri vardır. Aynı TV programlarını izlemezler veya aynı hobileri yoktur.Yüzyılın başında, TV programları günümüzdekinden daha önemliydi. Özellikle Ortadoğu kültüründe insanlar TV programlarını izlemek için bir araya geldiler. Bir pazarlama bilgisi olarak kolektif olmak, doğu kültüründe batı kültüründen daha önemlidir. Teknolojik gelişmelerle 2000'lerden sonra, insanlar daha evrensel hale geldi ve iletişim hiç olmadığı kadar kolaylaştı. İnternet hayatımızı kökten değiştirdi. YouTube yayın hayatına 2005 yılında başladı. YouTube ile insanlar kendi amatör videolarını tüm dünyada paylaşmaya başladı. İnsanlığın iletişimi için bir devrimdi.Bugün, '' YouTuber '' olarak adlandırılan birçok YouTube ünlüsü var. YouTube videolarıyla ünlü oldular. Ayrıca markalar, YouTube'u marka iletişimi ve reklam aracı olarak kullanıyor. YouTuberlar, görüntülenme oranları ve sponsorluk anlaşmalarıyla, normal bir iş için çok fazla para kazanıyor.YouTube'un analizi; pazarlama ihtiyaçları ve YouTube'daki gelişmeler nedeniyle bir zorunluluktur. Medya için uygulanan Kullanımlar ve Doyumlar Teorisi ve Değerler ve Yaşam Biçimi Sistemi YouTube’a bağlılığı ölçmek için uyarlanacaktır ve YouTube izleyicileri kesitlere bölünecektir. Bu tez ile, YouTube farklı bölümlere ayrılacak; böylece insanların alışkanlıklarını ve farklı her yaşam tarzlarını görebiliriz.

People live in different conditions and lifestyles. For marketing, observing the potential consumers movements is very crucial because brands decide their strategies with these predictions. Every consumer has their own unique characteristics. They don’t watch the same TV programs, or they don’t have same hobbies.In the beginning of the century, TV programs were more important than today. Especially in the Middle East culture people were became together to watch TV programs. As a marketing knowledge being collective is more important for the eastern culture than western culture. After the 2000s with technological improvements, people became more global and communication became easier than ever before. Internet has changed our lives from root. YouTube started its lifetime in 2005. With YouTube, people became to share their own amateur videos all around the world. It was a revolution for the communication of humanity.Today, there are a lot of YouTube celebrities that is called as ‘’YouTuber’’. They’ve became famous with their YouTube videos. Also, brands are using the YouTube for brand communication and as an advertisement tool. YouTubers are earning too much money for a regular job with their viewing rates and sponsorship agreements.Analyzing YouTube is a must due to marketing needs and developments of YouTube. Uses and Gratification Theory is a theory which is using for media and Values, Attitutes and Lifestyles theories adapted to measure loyalty to YouTube and segment to the YouTube audiences. With this thesis YouTube will be dividing into different segmentations, so we can see the habits of populations and every different lifestyle.
Keywords: Business; Demografik; Demographic; İşletme; Kullanımlar ve Doyumlar Teorisi VALS; Lifestyle; Loyalty; Sadakat; Uses and Gratification Theory; VALS; Yaşam Tarzı; YouTube